2023
DOI: 10.1111/1750-3841.16715
|View full text |Cite
|
Sign up to set email alerts
|

Use of coconut sugar as an alternative agent in osmotic dehydration of strawberries

Abstract: This study aimed to evaluate coconut sugar (CS) as an alternative osmotic agent to sucrose for the osmotic dehydration (OD) of strawberries. OD was performed by immersing strawberries cut into 13.6 ± 0.4 mm edge cubes in osmotic solutions of CS or sucrose, at two different concentrations (40% and 60%, w/w), with and without application of vacuum (AV) in the first 20 min of the process. The total OD time was 300 min. Evaluations of the kinetics of solid gain (SG), water loss (WL), and weight reduction (WR) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…where L*, a*, and b* are the luminosity, redness, and yellowness of the samples, respectively. Subscripts "t" and "0" refer to time t and zero time, respectively [31][32][33]. All the measurements were performed in triplicate.…”
Section: Physicochemical Properties' Determination During Osmotic Tre...mentioning
confidence: 99%
“…where L*, a*, and b* are the luminosity, redness, and yellowness of the samples, respectively. Subscripts "t" and "0" refer to time t and zero time, respectively [31][32][33]. All the measurements were performed in triplicate.…”
Section: Physicochemical Properties' Determination During Osmotic Tre...mentioning
confidence: 99%
“…The content of anthocyanins in the SA_US1_2 sample did not differ statistically from the content of these chemical compounds in the reference sample (SA_2), but this difference was relatively big (31.3%). Anthocyanins are chemical compounds characterized by relatively high solubility in water, so their reduced retention may stem from the leaching process occurring during osmotic dehydration [73]. Both non-thermal preliminary treatments cause structural changes in the treated tissue.…”
Section: The Influence Of Us or Pef Pretreatment On The Physical Prop...mentioning
confidence: 99%
“…It is worth mentioning that no statistically significant differences in the ascorbic acid content have been observed between sample SA_PEF2_2 and both US-treated samples. Vitamin C dissolves very well in water, which facilitates its leaching from the material during osmotic dehydration [73]. As mentioned above, cavitation could cause the disruption of covalent bonds and, as a result, the release of, e.g., ascorbic acid [69,70].…”
Section: The Influence Of Us or Pef Pretreatment On The Physical Prop...mentioning
confidence: 99%
“…It was observed that the use of coconut sugar instead of sucrose does not show any significant difference in its properties except pH and colour responses. The optimum results were observed with a 60% solution of coconut sugar [2] . To decrease the duration of osmotic dehydration and increase the efficiency of moisture removal from the fruits, ultra-sound assisted osmotic dehydration (UAOD) was explored by Salehi and his co-workers in Iran [3] .…”
Section: Introductionmentioning
confidence: 99%